Effects of microwave and mobile-telephone exposure on memory processes. - Lin, James C. (IEEE Antennas & propagation magazine.)
Three behavioral tests are described using rats to examine changes associated with learning and memory tasks, following microwave exposure. Working or short-term memory was measured via object discrimination, spatial memory was assessed using a radial-arm maze with food rewards, and spatial-reference learning and memory were measured using a circular water maze. The results indicate significant SAR-dependent decreases in object discrimination, significant variation with a spatial-learning and working-memory task in the radial-arm maze for two species of animals, and significant microwave-related impairments in spatial reference memory in a circular water maze at 1.2 W/kg. Deficits in the object-discrimination task were seen at 1 W/kg but not at 0.1 W/kg, both with no measurable microwave hyperthermia. Likewise, the behavioral measures of spatial memory also indicate a SAR-related response: no impairment at 0.05 W/kg but impairment at 0.6 W/kg.